Finite element simulation of square and circular polystyrene foam filled subjected to transverse quasi-static loading / Akbar Othman and - Othman, Akbar; Hasan, Mohd Fahrul (2012)
Thin-walled columns are used in a broad range of vehicular applications and especially as crash absorber elements. Crushing characteristics of absorbed energy in terms of quasi-static loading under transverse condition were crucial factors especially in finite element study. A numerical study is presented in this paper to investigate the energy absorption of polystyrene foam-filled on circular and square hollow 2024T aluminum alloy subjected to lateral compression. The failure mode of the polymeric foam-filled tube structures has been successfully simulated. The predicted compressive load displacement is in agreement with experimental results from reference literature. The energy absorption ability of the metallic structure due to plastic deformation in a crushing process is evaluated by comparison with the tube structure without filler. The results indicate that the energy absorption of a cellular material-filled tube structure is superior to the tube without filler